The Role of Health Higher Education Institutions in Developing Human Resources in The Digital Era - Purnomo Ananto; Kurnia Kusumawati; Renny Septiani Mokodongan (Poltanesa, 2026)
The rapid advancement of digital technology has transformed various sectors, including health higher education institutions, which are now required to produce human resources who are adaptive, competent, and prepared to face the demands of the digital health industry. The COVID-19 pandemic accelerated this transformation, promoting the adoption of technologies such as e-learning, telemedicine, and artificial intelligence in both education and healthcare service delivery. This study aims to systematically review recent literature on the strategic role of health higher education institutions in shaping students' digital competencies. A literature review method was applied, analyzing 24 national and international peer-reviewed articles published between 2019 and 2025 that address the digitalization of health education and human resource development. Findings indicate that digitalization not only enhances learning access and effectiveness but also opens opportunities for interdisciplinary collaboration, improves digital literacy, and supports the development of technology-based curricula. However, several challenges persist, including digital inequality, limited infrastructure, lack of faculty training, and data privacy concerns. Therefore, a strategic and collaborative approach involving educational institutions, technology providers, and healthcare stakeholders is essential to ensure that digital integration effectively prepares graduates who are relevant, adaptive, and globally competitive.